Burnout and Work Stress Effect on Performance: The Moderating Role of Social Support in the Food Industry - Silvia Listia Fadillah; Pipih Sopiah; Dedi Muhammad Siddiq; Mazlina Mamat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
With social support acting as a moderating factor, this study attempts to ascertain how employee performance is affected by burnout and work-related stress in the food business in Kuningan, Indonesia. Participants were given a standardized questionnaire as part of a quantitative survey approach. A statistical method was used to analyze the data and determine how the variables related to one another. Every participant gave their free and informed permission to participate in the study. Structural equation modeling (SEM) approaches were employed in data analysis to test the hypotheses made in the conceptual framework and assess the intricate relationships among study elements. In the context of the food processing business, empirical research supports a considerable negative link between employee performance and job stress and mental burnout. Additionally, social support effectively moderates the influence's strength, showing that while job stress and burnout have a detrimental impact on performance, social support can lessen those effects. These results highlight how crucial it is for businesses to prioritize the psychological health of their staff members and offer sufficient social support in order to boost worker productivity and performance in the food sector.